2019
DOI: 10.1242/dmm.033860
|View full text |Cite
|
Sign up to set email alerts
|

Pramipexole prevents ischemic cell death via mitochondrial pathways in ischemic stroke

Abstract: A dopamine D2 receptor agonist, pramipexole, has been found to elicit neuroprotection in patients with Parkinson’s disease and restless leg syndrome. Recent evidence has shown that pramipexole mediates its neuroprotection through mitochondria. Considering this, we examined the possible mitochondrial role of pramipexole in promoting neuroprotection following an ischemic stroke of rat. Male Wistar rats underwent transient middle cerebral artery occlusion (tMCAO) and then received pramipexole (0.25 mg and 1 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 49 publications
2
37
0
1
Order By: Relevance
“…it inhibits mitochondrial permeability transition pores, when given in nanomolar concentrations, by binding to the inner side of the mitochondrial membrane [43]. Mitochondrial mechanisms have been suggested to underlie antioxidant, antiapoptotic, neuroprotective efficiency of pramipexole which is visible already after its low doses [44,45]. It is currently unknown whether such non-dopaminergic mechanism indeed contributes also to the inhibitory influence of pramipexole on harmaline effects described in the present study and earlier [5] and to the tremorolytic effects of this drug in ET [21].…”
Section: Discussionmentioning
confidence: 99%
“…it inhibits mitochondrial permeability transition pores, when given in nanomolar concentrations, by binding to the inner side of the mitochondrial membrane [43]. Mitochondrial mechanisms have been suggested to underlie antioxidant, antiapoptotic, neuroprotective efficiency of pramipexole which is visible already after its low doses [44,45]. It is currently unknown whether such non-dopaminergic mechanism indeed contributes also to the inhibitory influence of pramipexole on harmaline effects described in the present study and earlier [5] and to the tremorolytic effects of this drug in ET [21].…”
Section: Discussionmentioning
confidence: 99%
“…PPX inhibits the early brain injury after subarachnoid hemorrhage ( Ma et al, 2016 ) and significantly reduces lipid peroxidation in a rat model of Parkinson's disease ( Zou et al, 2000 ). Recently, our laboratory reported that PPX post-treatment provides mitochondrial-mediated neuroprotection via closing mtPTPs in an ischemic stroke model ( Andrabi et al, 2019 ). Furthermore, pre-treatment of PPX protects PC12 cells treated with hydrogen peroxide through the activation of mitogen-activated protein ( Fujita et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of evidence has declassified such a fact that anti-apoptotic Bcl-2 and Bcl-x L can inhibit MPTP opening, whereas pro-apoptotic Bax and Bak proteins can stimulate MPTP opening (D'Orsi et al, 2017). Results from in vitro model of ischemic stroke in rats have shown that increased Bax/Bcl-2 ratio in ischemic insult could irritate MPTP opening, which may cause increased neuronal apoptosis (Andrabi et al, 2017;Andrabi et al, 2019). Actually, members in Bcl-2 family could also regulate two potential MPTP opening stimuli: Ca 2+ homeostasis and energy metabolism of neurons (D'Orsi et al, 2017;Peña-Blanco and García-Sáez, 2018).…”
Section: Causality Between Abnormal Mptp Opening and Apoptosis In Iscmentioning
confidence: 99%